Examination of Service Quality of Digital Payments among Working Professionals - Vaibhav Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: The major objective of this research study was to identify the different modes of digital payments which are popular among the working professionals. Further, there is an examination of the chosen variables of service quality related to digital payments in terms of their impact on the customer satisfaction. Methodology: This research has a conclusive research design. The independent variables were security, responsiveness, reliability and ease of use of digital payments done by working professionals in Delhi-NCR. Sample size taken was 373 and sampling technique used was stratified sampling. Online questionnaire distribution was done for data collection. The instrument was reliable and valid. Thematic analysis and multiple regression were applied as research techniques. Limitations: Due to Covid-19 and its regulations, opportunity of physical meeting or interactions with the respondents was mitigated. Resource limitation existed as an unavoidable element. Implications: This study has got practical as well as managerial implications. This study would provide valuable information to the marketers to devise the payment facility design by adhering to the relevant elements that can enhance customer satisfaction. It would even reflect upon the status of digital payments being adopted as a tool of financial payments by the working class and how it can shape the future market. It will add to the current set of literature as a useful study with immense future scope.